Ticket to Ride: I-deals as a Strategic HR Tool for an Employable Work Force - Van der Heijden, Beatrice; Nauta, Aukje; Fugate, Mel; De Vos, Ans; Bozionelos, Nikos (Frontiers in Psychology, 2021)
Abstract We describe how idiosyncratic deals (I-deals), in this case I-deals focused on workers’ employability enhancement, can serve as a powerful strategic HR tool for simultaneously meeting both the strategic goals of employers and the career goals of employees. Building on a sustainable career perspective, I-deals are interpreted as highly valuable, as they can help individual employees to more easily adapt to the fast-changing environments that nowadays characterize society and the labor market. After theoretical outlines on the concepts of I-deals and employability, we argue that I-deals can form the basis for integrative employment relationships aimed at employability enhancement. This article concludes with concrete recommendations for practice, indicating that in order to enable the sound use of I-deals as a strategic HR tool, organizations should discuss I-deals and employability openly through constructive dialogue. Moreover, examples for achieving this through specific practices, such as working with employability coaches and world cafés on employability, are described. Key words: I-deals, employability, sustainable career perspective, integrative employment relationship